Juridical Review of Legal Protection for Victims of Sexual Harassment as a Form of State Responsibility - Bachtiar Adi Prastyawan (Universitas Negeri Semarang, 2020)
Sexual harassment is a form of sexual violence and is classified as a serious crime. This is due to the impact of sexual harassment which can threaten and endanger the life of the victim. Seeing the impact that is the result of sexual harassment, it is necessary to protect victims of sexual harassment from several parties such as the government, institutions, families, and communities. In addition, there is a need for legal protection that is binding on victims of sexual harassment. This study aims to conduct a juridical review of legal protection for victims of sexual harassment as a form of state responsibility. The research method used is a normative approach with a normative legal research design. The data used are secondary data derived from important documents and literature related to the research topic. The results of this study are that there is already legal protection for victims of sexual harassment in Indonesia which is a form of state responsibility, namely Articles 5 6 of Law Number 31 of 2014 concerning amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims. , Law Number 35 of 2014 concerning Child Protection, and Law Number 39 of 1999 concerning Human Rights. This is also supported by the activeness of victim protection institutions that assist in the protection of victims of sexual harassment. The urgency of establishing legal protection for victims is to prevent and provide solutions to the impacts felt by victims of sexual harassment.